The fast azimuthal integration Python library: pyFAI - Ashiotis, Giannis; Deschildre, Aurore; Nawaz, Zubair; Wright, Jonathan P.; Karkoulis, Dimitrios; Picca, Frédéric Emmanuel; Kieffer, Jérôme (Journal of applied crystallography, 2015)
pyFAI is an open‐source software package designed to perform azimuthal integration and, correspondingly, two‐dimensional regrouping on area‐detector frames for small‐ and wide‐angle X‐ray scattering experiments. It is written in Python (with binary submodules for improved performance), a language widely accepted and used by the scientific community today, which enables users to easily incorporate the pyFAI library into their processing pipeline. This article focuses on recent work, especially the ease of calibration, its accuracy and the execution speed for integration.